2005
DOI: 10.1002/ange.200500365
|View full text |Cite
|
Sign up to set email alerts
|

Sequenzielle enzymatische Oxidation von Aminoarenen zu Nitroarenen über Hydroxylamine

Abstract: Die At‐Line‐Detektion einer von der N‐Oxygenase AurF katalysierten Aminooxidation liefert den ersten Nachweis für eine schrittweise enzymatische Oxidation von Aminoarenen zu Nitroarenen über ein Hydroxylamin‐Intermediat (siehe Schema). Die sequenzielle Natur dieser Reaktion wird durch die Biotransformation des Intermediats sowie die Identifizierung eines von p‐Aminobenzoat abgeleiteten Azoxy‐Nebenproduktes gestützt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Also being a member of the large fourhelix bundle protein family, AurF catalyzes the N-oxygenation of p-aminobenzoic acid to p-nitrobenzoic acid during the biosynthesis of the nitroaryl-substituted metabolite aureothin in S. thioluteus bacteria (Scheme 2). [13] Despite the fact that the activity of isolated AurF has been assessed up to now by using H 2 O 2 as the oxidizing agent, it is expected that the enzyme uses molecular oxygen under native conditions. [14] Similar to the R2 subunit of Chlamydia ribonucleotide reductases, it was originally assumed on the basis of sequence homologies that the new N-oxygenase AurF of S. thioluteus is a carboxylate-bridged diiron protein.…”
Section: Methodsmentioning
confidence: 99%
“…Also being a member of the large fourhelix bundle protein family, AurF catalyzes the N-oxygenation of p-aminobenzoic acid to p-nitrobenzoic acid during the biosynthesis of the nitroaryl-substituted metabolite aureothin in S. thioluteus bacteria (Scheme 2). [13] Despite the fact that the activity of isolated AurF has been assessed up to now by using H 2 O 2 as the oxidizing agent, it is expected that the enzyme uses molecular oxygen under native conditions. [14] Similar to the R2 subunit of Chlamydia ribonucleotide reductases, it was originally assumed on the basis of sequence homologies that the new N-oxygenase AurF of S. thioluteus is a carboxylate-bridged diiron protein.…”
Section: Methodsmentioning
confidence: 99%
“…[8] Herein we present the coordination sphere and catalyst geometry of the first reported Mndependent monooxygenase, the N-oxygenase AurF from Streptomyces thioluteus. [9][10][11][12] Recently we showed that AurF is able to selectively oxidize p-aryl amino groups to the corresponding nitro groups (Scheme 1). The enzyme can be applied in various ways-in vivo, in vitro, and immobilized in flow driven by H 2 O 2 -highlighting its potential application as a biocatalyst.…”
mentioning
confidence: 99%
“…[11,12] Nevertheless, it has been demonstrated for two structurally related dioxygenases that oxygen activation can be achieved by either metal. [13] What is quite striking is that the aureothin biosynthesis gene cluster does not contain any gene coding for components of an electron transfer chain, which usually consists of a ferredoxin, a ferredoxin reductase and NAD(P)H. [14] However, AurF has been proven to be active in vivo in at least three different organisms: in its natural host Streptomyces thioluteus, [15] as well as in the heterologous hosts Streptomyces lividans [7] and E. coli. [4] Moreover, the purified enzyme can be regenerated in vitro by using the peroxide shunt.…”
mentioning
confidence: 97%
“…[6] Through a number of in vivo and in vitro studies, we could show that Noxygenation of the amino substrates occurs stepwise and involves hydroxylamine and nitroso intermediates. [7] Furthermore, we could prove the participation of manganese in the catalytic action of AurF and were able to present the first X-ray structure of an N-oxygenase. [8,9] Later, another group reported the crystal structure of an iron-containing variant of AurF.…”
mentioning
confidence: 98%